2020
DOI: 10.1186/s40066-020-00257-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of variety attributes in the uptake of new hybrid bananas among smallholder rural farmers in central Uganda

Abstract: Background While advances in agricultural research and development have led to generation of improved new cooking hybrid banana varieties (HBVs) with enhanced yield potential to restore production levels, these have been received with mixed feelings on production and consumption attributes among the farming communities in Uganda. Some farmers prefer HBVs that are comparable to their local varieties in terms of consumption attributes such as soft food, color when cooked, flavor and taste while others prefer hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Sanya et al . (2020) also documented that better consumption attributes such as taste, texture and colour could increase the likelihood of adoption of improved banana hybrids by farmers in Uganda.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanya et al . (2020) also documented that better consumption attributes such as taste, texture and colour could increase the likelihood of adoption of improved banana hybrids by farmers in Uganda.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic variability for colour and biochemical parameters which can contribute to colour and texture changes during processing can be used for breeding and new hybrids should be evaluated for their processing quality. Sanya et al (2020) also documented that better consumption attributes such as taste, texture and colour could increase the likelihood of adoption of improved banana hybrids by farmers in Uganda.…”
Section: Important Quality Characteristics Of Plantain Food Productsmentioning
confidence: 98%
“…This result agreed with Kikulwe et al [46], who reported that taste and price are the most important factors for purchasing cooking banana in Uganda. Sanya et al [47] also documented that better consumption attributes such as taste, texture, and color could increase the likelihood of adopting improved banana hybrids by farmers in Uganda. Apart from taste, Ayinde et al [38] observed that size and number of fingers were considered the most important factors when purchasing plantain, while appearance, color, and shelf-life were the least.…”
Section: Factors Influencing Consumer's Choice and Their Willingness To Purchase New Plantain-based Productsmentioning
confidence: 99%
“…A possible explanation for women's interest in TC banana planting material could be attributed to the distinct role that women play in ensuring food security for their families. Food security in central Uganda is culturally viewed as a women's role, and women must ensure that their homesteads are food secure (Sanya et al [64]). The study finding is in line with Sanya et al [64], who found female farmers to be 12.4% more likely to adopt hybrid banana varieties compared to male farmers.…”
Section: Factors Associated With the Uptake Decision For Farmer Use Omentioning
confidence: 99%
“…Food security in central Uganda is culturally viewed as a women's role, and women must ensure that their homesteads are food secure (Sanya et al [64]). The study finding is in line with Sanya et al [64], who found female farmers to be 12.4% more likely to adopt hybrid banana varieties compared to male farmers. Nevertheless, with recent developments by the government being skewed to banana-based processing enterprises, it is likely that men will increasingly grow bananas to boost their sources of income.…”
Section: Factors Associated With the Uptake Decision For Farmer Use Omentioning
confidence: 99%